IMPLEMENTASI METODE PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF PESERTA DIDIK MATA PELAJARAN BAHASA ARAB DI MIN 11 BLITAR: IMPLEMENTASI METODE PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF PESERTA DIDIK MATA PELAJARAN BAHASA ARAB DI MIN 11 BLITAR - Eli Dwi Nabila, Eli Dwi Nabila; Afthon Ulin Nuha, Muhammad; Widayanti, Rizka; Musyafaah, Nurul; Sabilar Rosyad, Muh; Ni'mah, Mamluatun; Rondi, M.; Dr. Faedurrohman, M.Pd.I (Gerasi Insan Nusantara, 2025)
Learning methods play a vital role in education by helping teachers deliver material effectively. In today’s context, creative learning methods are essential to make lessons more engaging and meaningful. This study focuses on implementing the scramble-type cooperative learning method, integrated with the traditional game